Technology for designing structural-mental schemes for calculation tasks - N. I. Pak; E. V. Asaulenko (Открытое образование (Москва))
The purpose of the study. Modern teaching tools and methods, as a rule, implicitly rely on the “black box” model. In contrast, the “white box” model has clear didactic advantages. Unfortunately, they are difficult to implement in the educational process due to the lack of available ways to construct this model. The purpose of the study is to develop a technology for constructing a “white box” model in the form of a structural and mental scheme of calculation tasks in the field of elementary physics. This technology involves the use of calculation primitives to design task schemes by superposition.Materials and methods. Development of technology for constructing the “white box” model in the form of a structural and mental scheme of calculation tasks in the field of elementary physics. The use of calculation primitives to construct task schemes by superposition. Determining the complexity of a specific task through the number of primitives involved in the “route” of the solution. Organization of students’ training according to the “white box” model with visualization of the process of forming skills to solve calculation tasks.Results. Schemes have the ability to ensure the strength and completeness of the formation of the ability to solve problems of the student. At the same time, the variety of routes and the set of weights of the paths make up the information model of learning. As an example, structural and mental schemes on the topic “thermal phenomena” are presented. They show the need to use several types of primitives, in particular, function primitives, sum primitives. Structural and mental schemes allow students to organize training according to the “white box” model, visualize the process of formation and development of students’ skills to solve calculation tasks, thereby ensuring control and self-control of educational activities.Conclusion. Based on the provisions of the mental approach, a technology for constructing structural and mental schemes representing a cognitive way of thinking in solving computational problems is proposed. The basic technology is computational primitives, with the help of which problem schemes are constructed by superposition. The complexity of a particular task is determined by the number of primitives involved in the “route” of the solution. The proposed technology is applicable to the construction of structural and mental schemes of computational problems in various subject areas.